Font Size: Small Medium Large The Staff Planning for The Second Category of Honorary Employees in Bogor Regency - Augustine, Leonita; Jannah, Lina Miftahul (UI Scholars Hub, 2015)
The purpose of this journal is to describe the staff planning for a second category of honorary employees who are not qualified to be civil servants in the Bogor Regency. The issue of staff planning in the public sector is important because the employees need to achieve the mission of public sector to response the demands of society and to meet the public's needs. The result of this research can be used as the recommendations to the central government, Bogor Regency Administration, and other local governments in efforts to face the second category of honorary employees who are not qualified to be civil servants. The method of this research is a qualitative approach. This research uses in-depth interviews with purposive technique and study document. The result shows that staff planning of Bogor Regency Administration is to re-employ the second category of honorary employees who are not qualified to be public servants. This staff planning is based on environment, forecasting, purposes, plans, and support from Bogor Regency Administration, but needs to consider the existence of Draft of Regulation about Civil State Apparatus (RUU ASN); regional minimum wages and insurance; training and development; and limitation of working age.